TOURISM POLICY OF UZBEKISTAN IN 1945-1991 - Ernazarov Fayzullo Narzullaevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
World experience shows that the socio-political, economic and cultural development of countries is largely dependent on their attitude to tourism. Some countries in the world, based on their capabilities, ensure the economic stability of the country at the expense of income generated by the development of tourism. Tourism, by its very nature, also plays a significant role in the development of inter-civilizational harmony. As we study the history of tourism in depth, we can determine the future priorities of this sector. This article was prepared taking into account these aspects, and historical facts about the main features, problems, shortcomings and achievements of tourism policy in Uzbekistan in 1945-1991 were studied and analyzed. Also, while reading the article, a clear picture of the tourism policy of Uzbekistan in 1945-1991 will emerge.